Altered negative priming in older subjects: first evidence from behavioral and neural level - Bauer, Eva; Gebhardt, Helge; Gruppe, Harald; Gallhofer, Bernd; Sammer, Gebhard (Frontiers in Human Neuroscience, 2012)
The impact of aging on the negative priming (NP) effect has been subject of many studies using behavioral measures. Results are inconsistent and corresponding neural data do not exist. We were interested in, whether or not processing of NP is altered in older in comparison to young adults on behavioral and neural level. NP is of special interest, because it measures the ability of inhibiting distractors indirectly, allowing drawing serious conclusions regarding the aging brain. Eighteen young and eighteen older healthy adults performed a location-based NP paradigm during fMRI. Young adults behaviorally showed a NP effect and NP associated fronto-striatal activation, which is in accordance with the inhibitory model of NP. In older subjects no significant behavioral NP effect and no NP related activation in predefined brain regions could be found. Hence, NP evokes no compensatory overactivation like other, non indirect inhibitory tasks. This is explained with the absence of the behavioral effort bias in NP, which might play a role in other tasks. One possible source for the lack of NP related activation is a reduction of gray matter volume in older subjects as shown using voxel based morphometry (VBM).